2015
DOI: 10.1080/13607863.2014.995593
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of self-efficacy on the relation between behavior problems in persons with dementia and the distress they cause in caregivers

Abstract: The results suggest that self-efficacy for managing BPSD attenuates the relation between the frequency of behavior problems – both disruptive and depressive – and the distress they cause in caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…This association is also in agreement with Nogales‐Gonzales et al . (), who found that competence moderated the relationship between BPSD frequency and reactivity to BPSD. The fit of the model after Step 1 was χ 2 = 32.8, df = 20, p = 0.036, CFI = 0.967, NFI = 0.918 and RMSEA = 0.064, indicating that the model still did not fit the data, as reported in the Supporting information Figure S2.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This association is also in agreement with Nogales‐Gonzales et al . (), who found that competence moderated the relationship between BPSD frequency and reactivity to BPSD. The fit of the model after Step 1 was χ 2 = 32.8, df = 20, p = 0.036, CFI = 0.967, NFI = 0.918 and RMSEA = 0.064, indicating that the model still did not fit the data, as reported in the Supporting information Figure S2.…”
Section: Resultsmentioning
confidence: 96%
“…() suggested that competence was a buffer against burden, because caregivers with greater levels of competence had more positive gains and experienced less burden when confronted with BPSD. Furthermore, the novel association between competence and reactivity to BPSD is partially supported by previous research whereby competence was found to moderate the relationship between BPSD frequency and reactivity to BPSD (Nogales‐Gonzales et al ., ). More research is necessary to fully understand this association.…”
Section: Discussionmentioning
confidence: 97%
“…The success of the current program in meeting caregiver needs around BPSD may have been an important factor in ensuring caregiver burden did not increase and that people with dementia remained living at home. Further to this, self-efficacy amongst caregivers is associated with a reduced burden associated with frequent BPSD (Nogales-González et al, 2015). Although our evaluation did not include a direct measure of self-efficacy, increased knowledge can improve self-efficacy (Nogales-González et al, 2015) and meeting needs may have been a driver in the usefulness of the GTSAH program.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, self-efficacy amongst caregivers is associated with a reduced burden associated with frequent BPSD (Nogales-González et al, 2015). Although our evaluation did not include a direct measure of self-efficacy, increased knowledge can improve self-efficacy (Nogales-González et al, 2015) and meeting needs may have been a driver in the usefulness of the GTSAH program. Including a measure of self-efficacy in future studies could provide a direct test of this assertion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CSE has moderating effects on physical and psychological health as well as the coping ability of caregivers . High CSE is associated with lower caregiver burden, more positive gains such as a sense of purpose, and fewer depressive symptoms and distress . When taking care of PWD, CSE seems to act as the caregiver's personal resource that mediates other caregiver outcomes, such as caregiving burden and depression .…”
Section: Introductionmentioning
confidence: 99%